2015
DOI: 10.1249/01.mss.0000478899.71973.c8
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes Of Different Tempos Of Music During Exercise In Cardiac Rehabilitation Patients

Abstract: International Journal of Exercise Science 10(5): 681-689, 2017. This study examined the effects of stimulating and sedative music on ratings of perceived exertion (RPE), heart rate (HR), blood pressure (BP), and feeling status during exercise in cardiac rehabilitation (CR) patients. Twenty-two male and female older adults age 64 ± 8.0 y currently enrolled in phase III CR completed the study. Repeated measures crossover designs guided data collection. The manipulated independent variable was music condition (se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(27 citation statements)
references
References 14 publications
0
27
0
Order By: Relevance
“…[52] In contrast, another study, using sedative and stimulating music among cardiac rehabilitation patients, showed no effect of the type of music on BP. [53] In another study, the HR and BP changes were not correlated with the music preference of the participants. [54] Further, active music therapy reduced LF/HF while passive listening (as seen in the present study) increased LF/HF.…”
Section: After Interventionmentioning
confidence: 92%
“…[52] In contrast, another study, using sedative and stimulating music among cardiac rehabilitation patients, showed no effect of the type of music on BP. [53] In another study, the HR and BP changes were not correlated with the music preference of the participants. [54] Further, active music therapy reduced LF/HF while passive listening (as seen in the present study) increased LF/HF.…”
Section: After Interventionmentioning
confidence: 92%
“…Self-selected sedative music has been shown to induce both aroused and sedative emotions and a slight but significant increase in HR (63). In contrast another study, using sedative and stimulating music among cardiac rehabilitation patients, showed no effect of the type of music on BP (64) (66,67). When HRV was analysed during no sound condition RMSSD significantly increased, which authors attributed to the supine posture, when cardiac PNS inputs were maximal (68).…”
Section: Discussion Of Main Findingsmentioning
confidence: 99%
“…Apart from the group education, a hospital plus home-based heart-healthy exercise will be implemented by the researcher with the support of a physiotherapist, registered nurse, and medical officer at the study hospital’s cardiology clinic. On day one in the first week of the intervention, participants will be guided to perform the exercise (warm-up exercise, brisk walking, and cool-down exercise) with cultural background music (Raravenu Gopabala Instrumental flute version) to perform the exercise at the prescribed intensity and duration and reduce the rating of perceived exertion during exercise [ 37 , 38 ] under the supervision of a physiotherapist. As suggested by the cardiologist, the exercise will start at low intensity with cultural background music with a slow tempo (40–60 beats per minute).…”
Section: Methodsmentioning
confidence: 99%